Metal Oxide Coated Lithium Cobalt Fluorophosphate Cathode Materials for Lithium Secondary Batteries-Effect of Aging and Temperature - Amaresh, S.; Karthikeyan, K.; Kim, K. J.; An, J. Y.; Cho, S. J.; Chung, K. Y.; Cho, B. W.; Nam, K. W.; Lee, Y. S. (AMER SCIENTIFIC PUBLISHERS, 2014)
Lithium cobalt fluorophosphate (Li2CoPO4F) is a promising 5 V class cathode material for lithium secondary batteries. In this study, surface coating with ZrO2 improved the electrochemical activity of Li2CoPO4F with a maximum discharge capacity of 144 mA h g(-1). The effectiveness of ZrO2 coating was evaluated using aging analysis with a commercial electrolyte, i.e., 1 M LiPF6 in EC:DMC (1:1, v/v). The metal ion dissolution was reduced to 1/8th of that observed in the non-coated Li2CoPO4F. It was found that the thin coating layer had less or no contribution to the additional resistance for the cell, both at an open circuit potential and at a fully charged state; hence, the capacity of the cell was retained over cycling. Elevated temperature aging did not affect the intrinsic property of the coated Li2CoPO4F, as observed from the complete anodic and cathodic peaks from cyclic voltammetry studies after 30 days of storage at 50 degrees C. An increase in impedance was observed for aged cells, which could be due to the thick SEI layer formed during storage. The ZrO2 coating over Li2CoPO4F was crucial for the improved performance of electrode active material at higher operating potentials of up to 5.2 V.
Keywords: ELECTROCHEMICAL PERFORMANCE; LI2COPO4F; ELECTRODES; LIXCOO2